Analysis of The Effects of Time Budget Pressure, Audit Fee, Auditor Switching, and Auditor Specialization on Audit Quality - Jelita, Vannya Puspa; Arum, Enggar Diah Puspa; Olimsar, Fredy (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2026)
Introduction/Main Objectives: This study aims to test and analyze the simultaneous and partial effects of time budget pressure, audit fee, auditor switching, and auditor specialization on audit quality in consumer finance and insurance companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Background Problems: The phenomenon of audit failures at several financial services companies serves as the background to this issue, raising the question of whether these four variables influence audit quality. Novelty : The novelty of this study lies in the combination of these four variables within the context of consumer finance and insurance companies during the post-pandemic period, an area that has been rarely explored. Research Methods: This study employs a quantitative approach using multiple linear regression analysis and descriptive statistics, utilizing secondary data in the form of audited financial statements and annual reports from the 2020–2024 period, processed using SPSS version 26. Finding/Results: The results indicate that time budget pressure, audit fee, auditor switching, and auditor specialization simultaneously influence audit quality. Time budget pressure significantly impacts audit quality, audit fee significantly impacts audit quality, auditor switching doesn't significantly impact audit quality, auditor specialization doesn't significantly impact audit quality. Conclusion: audit quality is jointly determined by these four variables. Public accounting firms need to manage time budgets carefully and ensure adequate audit costs, while mandatory rotation policies and auditor specialization need further evaluation because, individually, they do not guarantee improved audit quality in this study.